Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.celrep.2018.06.120
|View full text |Cite
|
Sign up to set email alerts
|

Pol V-Mediated Translesion Synthesis Elicits Localized Untargeted Mutagenesis during Post-replicative Gap Repair

Abstract: In vivo, replication forks proceed beyond replication-blocking lesions by way of downstream repriming, generating daughter strand gaps that are subsequently processed by post-replicative repair pathways such as homologous recombination and translesion synthesis (TLS). The way these gaps are filled during TLS is presently unknown. The structure of gap repair synthesis was assessed by sequencing large collections of single DNA molecules that underwent specific TLS events in vivo. The higher error frequency of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 66 publications
2
40
0
Order By: Relevance
“…In contrast, repriming of DNA replication downstream of the lesion, leaves a long ssDNA gap (>200 nucleotides) that is repaired primarily by a highfidelity recombination-dependent gap filling mechanism. However, a small fraction of these gaps are filled in by the combined actions of replicative and TLS polymerases in a highly mutagenic manner (TLS at the gap) (Isogawa et al, 2018). This widespread mutagenesis that results during TLS at the gap is more likely to lead to functional genetic alterations compared with the localized mutagenesis that occurs adjacent to the lesion during TLS at the fork.…”
Section: Resolution Pathway Choice and Mutagenesismentioning
confidence: 99%
“…In contrast, repriming of DNA replication downstream of the lesion, leaves a long ssDNA gap (>200 nucleotides) that is repaired primarily by a highfidelity recombination-dependent gap filling mechanism. However, a small fraction of these gaps are filled in by the combined actions of replicative and TLS polymerases in a highly mutagenic manner (TLS at the gap) (Isogawa et al, 2018). This widespread mutagenesis that results during TLS at the gap is more likely to lead to functional genetic alterations compared with the localized mutagenesis that occurs adjacent to the lesion during TLS at the fork.…”
Section: Resolution Pathway Choice and Mutagenesismentioning
confidence: 99%
“…With respect to error-free bypass of G-AAF by Pol V, TLS is stimulated (~7 fold) in the dnaQ( Q*) strain compared to the mutD5 strain ( Figure 5D), in good agreement with the data observed for Pol V-mediated TLS across TT-CPD and TT(6-4) lesions. Productive TLS, requires Pol V to remain bound to the primer P/T junction in order to synthesize a TLS patch rather than to only insert a single nucleotide directly across from the lesion site Isogawa et al, 2018). As weakening the ε-cleft interaction in cells significantly increased the utilization of TLS over cognate lesions for all three TLS polymerases, we conclude that the ε-cleft contact acts as a gatekeeper to regulate access to the P/T junction.…”
Section: The ε Subunit Acts As a Gatekeeper For All Three E Coli Tlsmentioning
confidence: 82%
“…This gap-suppressing effect of TLS at the fork may play a pivotal role in determining the extent of damage-induced mutagenesis. A recent study has demonstrated that damage-induced mutagenesis is not limited to the lesion site but instead can spread a few hundred nucleotides from the lesion (72). This extended patch of low-fidelity synthesis likely results from gap filling synthesis where bypass of the lesion by the cognate TLS polymerase is followed by the sequential action of multiple polymerases, including the highly mutagenic Pol V, to fill in the remaining ssDNA gap (Fig.…”
Section: Repriming Is a Failsafe Mechanism For Rescuing Stalled Replimentioning
confidence: 99%